Sustainable Finance Practices and Application in Commercial Banks: A Phenomenological Study (Global Journal of Management and Business Research, 2022)
As a new practice in finance world communities are incorporating environmental social and governance ESG interests into our financial practice terming it as Green Fianc ESG s core concept and the United Nations Sustainable Development Goals 2030 help spread this west evolved concept to developing countries
Keywords: green finance; sustainable finance; sustainable development goals; nepalese commercial banking